Chemical optimization towards superior electrocatalysis of Janus 1T-MoSX (X = O, Se, Te) for hydrogen evolution: Small composition tuning makes big difference. (1st July 2019) - Hao, Yu; Xu, Li-Chun; Yang, Zhi; Liu, Rui-Ping; Li, Xiu-Yan; Pu, Jibin; Huang, Liang-Feng
Abstract: Transition metal dichalcogenides (TMDs) can be used as promising nonprecious catalysts for hydrogen evolution reaction (HER), but there has still been a problem of inert basal plane. Inspired by a recent progress in the experimental preparation and characterization of the sandwiched monolayer (ML) Janus MoSSe, we use first-principles methods to explore the stability and HER activity of Janus ML 1T-MoSX (X = O, Se, Te) and optimize the HER activity by tuning the content of anionic X atom. According to the calculated thermodynamic and kinetic properties, we find that both excellent stability and high catalytic performance of 1T-MoSX can be simultaneously obtained when the content of X atom on surface reaches 0.22. Among different types of X, the introduction of O can yield the most favored adsorption energy of H adatom, the lowest kinetic activation energy for the H desorption, and the largest exchange current density ( i 0 ) for the HER of 1T-MoSX. It is a remarkable and important finding that the i 0 of 1T-MoSX is in the same magnitudinal order as that of the precious Pt electrode. The electronic-structure mechanism underlying the superior HER performance of 1T-MoSX is also analyzed in depth. This work indicates a promising application of the new 1T-phase TMDs in high-performance HER catalysis, and the chemical trends present here can also be readily validated by future experiments.